Selective Separation of MA(III) from Ln(III) by Highly Stable Silica-Polymer-based N-Donor IsoBu-BTP/SiO2-P Adsorbent. Issue 2 (23rd February 2019) - Ning, Shunyan; Zhang, Wei; Yu, Shuqi; Zhang, Shichang; Zhou, Jie; Wang, Xinpeng; Wei, Yuezhou
ABSTRACT: To separate minor actinides (MA) from lanthanides from high-level liquid waste (HLLW), a kind of micro-porous silica-polymer (SiO2 - P ) based N-donor iso Bu-BTP/SiO2 - P adsorbent was synthesized and characterized. The efficient separation of 241 Am(III) over Ln(III) lighter than Dy(III) was achieved in both batch and column experiments in pH 2–NaNO3 medium. The γ-irradiation stability of iso Bu-BTP/SiO2 - P was evaluated with the maximum absorption dose reaching to 207 kGy followed by TOC, UV, and UPLC/Q-TOF-MS analysis, which revealed good γ-irradiation stability of iso Bu-BTP/SiO2 - P . Furthermore, the adsorption mechanism was studied using XPS and EXAFS, which revealed that the interaction between Eu(III) and iso Bu-BTP/SiO2 - P mainly happened to the N atoms in iso Bu-BTP. In a word, iso Bu-BTP/SiO2 - P is a very promising candidate for separating MA(III) from Ln(III) in pH 2–NaNO3 medium.